Study on Energy Consumption Optimization Scheduling for Internet of Things - Xuefeng Ding (IEEE Access, 2019)
In the complex working environment of the Internet of Things (IoT), there are many differences in the work between many devices, as well as complex associations and energy constraints. The entire task scheduling system needs to consume a large amount of energy for communication. In order to describe its relevance and constraint relationship, traditional scheduling modeling methods need to add a large number of constraints. In this paper, an energy loss optimization scheduling modeling method based on the multi-objective fuzzy algorithm is proposed. Based on the equipment scheduling energy cost and equipment scheduling time in the IoT environment, the multi-objective equipment scheduling optimization equation in the IoT environment is constructed, and the fuzzy algorithm is integrated into the single-target energy loss problem. The algorithm searches for the idle time of the device and optimizes the device scheduling energy consumption model to reduce the overall energy consumption of the device scheduling in the IoT environment. The experimental results show that based on the multi-objective fuzzy algorithm, the equipment scheduling modeling method in the IoT environment considering energy loss has the characteristics of high precision and energy saving.